2013
DOI: 10.19030/jber.v11i12.8260
|View full text |Cite
|
Sign up to set email alerts
|

Market And Welfare Effects Of Multi-Product Mergers With Reference To Tyson-IBP Merger

Abstract: In this paper, we provide a conceptual framework for analyzing the market and welfare effects of mergers that result in multiproduct firms producing strongly demand-related products and derive the conditions under which such type of mergers improve welfare. The Tyson-IBP merger is used as an empirical application of the model. Using estimates of own- and cross-price elasticities of demand for beef, pork, and chicken, we infer that the Tyson-IBP merger has generated the cost-efficiencies necessary to make consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…For the empirical part of this study, the linear inverse market demand relationships are expressed by equations (23) and (24). Bouras (2007) and Bouras and Azzam (2013) set α x = α y = 1 . In order to avoid corner solutions and with no loss of generality, the present work sets the constant parameters, in both demand equations, equal to 10.…”
Section: Model Calibration Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the empirical part of this study, the linear inverse market demand relationships are expressed by equations (23) and (24). Bouras (2007) and Bouras and Azzam (2013) set α x = α y = 1 . In order to avoid corner solutions and with no loss of generality, the present work sets the constant parameters, in both demand equations, equal to 10.…”
Section: Model Calibration Results and Discussionmentioning
confidence: 99%
“…These findings indicate that mergers between firms producing demand-related goods, under certain conditions, may foster collusion. Bouras and Azzam (2013) analyzed the market and welfare effects of the Tyson-IBP merger. The authors concluded that the merger has produced cost efficiencies necessary to make consumers and livestock producers better off.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations